An exploratory investigation of the body image and health behavior transition in retiring intercollegiate athletes - Galli, N.; Shodahl, S.; Otten, M. P. (Journal of Clinical Sport Psychology, 2024)
Because an athletes` body is central to their identity, it is important to consider the ramifications of retirement from sport on their well-being. Using a single-group pre-post test design, the purpose of this exploratory study was to expand on the current state of knowledge regarding the body image and health behavior transition of retired intercollegiate athletes. Ten athletes from three institutions completed demographic and health behavior questions, the Body-Image Ideals Questionnaire, and selected items from the Body Parts Satisfaction Scale-Revised online prior to and after retirement (M = 305 days). Although most athletes reported maintaining healthy patterns of nutrition and physical activity in retirement, results showed that body satisfaction significantly declined, and that actual-ideal body discrepancy increased, albeit to a nonsignificant degree. National Collegiate Athletic Association athletics departments to consider how they can more effectively empower athletes to take care of and appreciate their body even after the final performance.